Evaluation of Nicorandil in Treatment of induced pulmonary arterial hypertension in male Rats - Taha Hashim Ahmed; Israa Burhan Raoof; Bahir Abdul-Razzaq Mshemish (College of Pharmacy / Mustansiriyah University, 2024)
Pulmonary arterial hypertension (PAH) is a chronic, rare, and non-treatable disease, resulting in elevated mean arterial pressure (≥25mmHg) during rest and (≥30mmHg) during exercise.    Pulmonary arteries remodeling including endothelial apoptosis, smooth muscle hyperplasia, and endothelial dysfunction are distinct features of PAH. This study aims to evaluate effect of nicorandil as an alternative treatment for PAH in comparison to tadalafil by evaluating its anti-inflammatory effect and histopathological changes. A total of 60 male wistar rats were divided to 6 groups, a control healthy group, and another 5 groups injected with monocrotaline to induce PAH. The induction group was left untreated while the other 4 groups were treated with either nicorandil or tadalafil, with or without treatment blockers (N-Nitroarginine methyl ester and glimepiride), after 21 days they were sacrificed for histopathology and measurement of inflammatory markers. Nicorandil reduced the levels of osteopontin, and cardiac marker brain natriuretic peptide (BNP) significantly (P≤0.05) , also it showed an improved histopathological picture of PAH by reducing smooth muscle proliferation, necrosis, and inflammation in pulmonary arteries. In conclusion, nicorandil in this study showed promising results in reducing inflammation and improving endothelial function.